Modified aluminate cement, carbon sequestered phosphoaluminate cement and preparation methods of modified aluminate cement and carbon sequestered phosphoaluminate cement

Through the ore phase composition and phosphate complexing of modified aluminate cement, the mechanical properties of silicate cement deteriorated under CO2 corrosion and uncontrollable compounding of calcium aluminate cement in the prior art are solved, and the problem of uncontrollable compounding of calcium aluminate cement in the prior art is achieved. The high strength, CO2 corrosion resistance and adjustable settling time of carbon sequestration aluminate cement are suitable for carbon sequestration and repair applications.

CN119263661APending Publication Date: 2025-01-07NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411492548.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The mechanical properties of existing silicate oil well cement deteriorated under CO2 corrosion conditions, which cannot meet the long-term storage requirements of CO2. Moreover, the settling time and thickening properties of calcium aluminate cement and phosphate compounded with calcium aluminate cement are uncontrollable, affecting the engineering application.

Method used

Modified aluminate cement is used, and the ore phase composition includes CA: 20%~55%, CA2: 10%~50%, C2AS: 25%~35%, C12A7: 0.1%~0.2%, and the CA/CA2 ratio is regulated. Combined with phosphate, carbon-sealed aluminate cement with CO2 corrosion resistance, high strength and adjustable settling time were prepared.

Benefits of technology

The engineering performance optimization of aluminate cement has been achieved, with adjustable settling time, early strength and late strength, and CO2 corrosion resistance, which reduces the preparation cost, and has anti-seepage, sulfate corrosion resistance, high temperature resistance and freezing resistance. Performance, suitable for carbon storage and repair applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263661A_ABST
    Figure CN119263661A_ABST
Patent Text Reader

Abstract

The invention discloses modified aluminate cement, carbon sequestered phosphoaluminate cement and a preparation method, based on the mineral phase activity and hydration characteristics of aluminate cement, the mineral phase content of CA and CA2 in the aluminate cement and the (CA / CA2) ratio are regulated and controlled within the range of 0.5-1.5, mineral phase matching is optimized, and the engineering performance of the phosphoaluminate cement is improved. The phosphoaluminate cement obtained by compounding the modified aluminate cement, phosphate and an admixture has adjustable setting time, high early strength and later strength and excellent CO2 corrosion resistance, and a novel cementing material is provided for carbon sequestration. And meanwhile, the concrete also has excellent anti-permeability, sulfate corrosion resistance, high temperature resistance, freezing resistance and repairing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement, and in particular relates to modified aluminate cement, carbon-sequestered aluminophosphate cement and a preparation method thereof. Background Art

[0002] Carbon capture, utilization and storage (CCUS) technology has become an indispensable key technology for my country to achieve its carbon neutrality goal. The integrity of the CCUS cementing cement ring is the key to ensuring the sealing of the wellbore, which directly affects the safety and long-term effectiveness of CO2 geological storage wells. Silicate oil well cement has a high alkalinity characteristic, and its hydration products such as calcium hydroxide and CSH gel are easily corroded by acidic media (CO2). Under long-term service CO2 corrosion conditions, the mechanical properties of the cementing cement ring will degrade and cannot meet the long-term CO2 storage requirements. Aluminophosphate cement (CAPC) has the characteristics of low alkalinity, early strength, high strength, water resistance, high temperature resistance and chemical corrosion resistance, and can be used as a carbon storage material system.

[0003] Aluminophosphate cement is a biocement material with high long-term strength and stable hydration products (hydroxyapatite). However, its main mineral, tricalcium phosphate, reacts slowly with water at room temperature and has low early strength. Li Shiqun et al. explored the CaO-Al2O3-P2O5 ternary phase diagram by using the partition test method and synthesized a hydraulic material containing a new phase by the sol-gel method. Its mineral composition is Li Hu (LHss) solid solution phase (considered to be aluminophosphate solid solution), monocalcium aluminate (CA), dicalcium aluminate (C2A), tricalcium phosphate (C3P) and a small amount of glass phase, which was later called aluminophosphate cement.

[0004] At the same time, calcium aluminate phosphate cement can be prepared by compounding calcium aluminate cement (CAC) and phosphate as the main raw materials. The acid-base reaction between phosphate and calcium aluminate phase forms hydration products and produces strength. Calcium aluminate cement is the main basic material of calcium aluminate phosphate cement, which is mainly composed of monocalcium aluminate (CA), dicalcium aluminate (CA2), dodecaluminate (C 12 A7) and calcium aluminum feldspar (C2AS) and other mineral phases, with fast hydration rate, and the characteristics of resistance to sulfate erosion, good refractory performance, and rapid early strength development. Both monocalcium aluminate and calcium dialuminate phases have the characteristics of fast hydration rate and high activity, among which monocalcium aluminate has a faster hydration rate and higher activity. At present, the setting time and thickening performance of calcium phosphate aluminate cement made by compounding calcium aluminate cement with phosphate are uncontrollable, which seriously affects the engineering application of calcium phosphate aluminate cement. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a modified aluminate cement in view of the deficiencies in the prior art, and to compound the modified aluminate cement with phosphate to obtain carbon-sequestered aluminophosphate cement, which has the characteristics of resistance to carbon dioxide corrosion, high strength, and adjustable setting time and thickening properties.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A modified aluminate cement, wherein the mineral phase composition is calculated by mass percentage, including CA: 20%~55%, CA2: 10%~50%, C2AS: 25%~35%, C 12 A7: 0.1%~0.2%. CA / CA2=0.5~1.5 is preferred.

[0007] Furthermore, the present invention also provides a method for preparing the modified aluminate cement, comprising the following steps: (1) crushing, drying, grinding and fully mixing the calcium raw material and the aluminum raw material to obtain raw material; (2) The uniformly mixed raw material is heated to 800-950°C and kept at this temperature for 20-40 minutes, then heated to 1300-1600°C and calcined for 30-100 minutes. After calcination, it is quickly cooled to obtain cement clinker blocks; (3) Grind the obtained cement clinker blocks and mix them thoroughly to obtain the cement clinker.

[0008] Specifically, in step (1), the calcium raw material is at least one of limestone, quicklime or slaked lime, preferably limestone; the aluminum raw material is at least one of bauxite, aluminum ash and aluminum-containing waste slag, preferably bauxite and aluminum ash.

[0009] Specifically, in step (1), the calcium raw material contains 40% to 55% by mass of CaO; the aluminum raw material contains 50% to 70% by mass of Al2O3; and the raw material is configured according to a mass composition of 30% to 40% CaO and 50% to 65% Al2O3.

[0010] Specifically, in step (2), the temperature is first increased to 800-950°C at a heating rate of 5-15°C / min, kept at that temperature for 30 minutes, and then increased to 1300-1600°C at a heating rate of 5-15°C / min, and kept at that temperature for 30-100 minutes.

[0011] Specifically, in step (2), after calcination, the mixture is rapidly cooled to room temperature by air cooling, water cooling or liquid nitrogen cooling.

[0012] Furthermore, the present invention also provides a carbon-sequestered aluminophosphate cement, which is mixed with the above-mentioned modified aluminate cement, phosphate and admixture; wherein the mass percentage of phosphate is 5%~15%, the mass percentage of admixture is 5%~20%, and the rest is modified aluminate cement.

[0013] Specifically, the phosphate is at least one of trisodium phosphate, sodium dihydrogen phosphate, sodium polyphosphate, tripolyphosphoric acid, sodium metaphosphate and sodium hexametaphosphate.

[0014] Specifically, the admixture is at least one of fly ash, slag and silicon powder.

[0015] Furthermore, the present invention also claims a method for preparing the above carbon-sequestered aluminophosphate cement, comprising the following steps: (1) Grinding the modified aluminate cement and passing it through a 74µm sieve; (2) The modified aluminate cement sieved in step (1) is compounded with phosphate and admixtures, and the mixture is placed in a ball mill and mixed evenly to obtain a cement slurry.

[0016] Compared with the prior art, the present invention has the following beneficial effects: First, based on the mineral phase activity and hydration characteristics of aluminate cement, the present invention regulates the content of CA and CA2 mineral phases and the ratio of (CA / CA2) in aluminate cement within the range of 0.5-1.5, optimizes the mineral matching, and improves the engineering performance of phosphate aluminate cement. The CA phase in the mineral phase of aluminate cement is beneficial to the early strength development of cement, but will lead to rapid setting of cement and reduced later strength; the CA2 phase is beneficial to the later strength development of cement; C 12 A7 is prone to cause cement to set quickly, and the strength in the later stage is reduced. This project regulates aluminate cement to have a higher content of CA and CA2 mineral phases, and controls the CA / CA2 mineral phase ratio to 0.5~1.5, and a lower content of C 12 A7, which makes the setting time of phosphate aluminate cement adjustable and has excellent mechanical properties.

[0017] Second, the present invention uses modified aluminate cement and phosphate to prepare phosphate aluminate cement, first adjusts the mineral phase composition and activity of aluminate, and then compounds with phosphate to synergistically adjust the reaction activity, reaction rate and hydration performance of phosphate aluminate cement. Compared with the direct calcination preparation of phosphate aluminate cement, the engineering performance of the phosphate aluminate cement compounded with modified aluminate cement and phosphate proposed in this patent is easier to adjust, and the engineering performance of phosphate aluminate cement can be adjusted by changing the mineral phase composition content of aluminate cement, the type and content of phosphate, and the type and amount of admixtures, so that it is suitable for engineering applications such as CO2 corrosion resistance and repair.

[0018] Third, the present invention uses a low amount of phosphate (5% to 15%), which effectively reduces the preparation cost of phosphate aluminate cement. In the prior art, commercial aluminate cement and phosphate reagent are compounded to prepare phosphate aluminate cement, wherein the amount of phosphate reagent is 15% to 40%, which makes the preparation cost of phosphate aluminate cement high. The present invention regulates and modifies the composition content of aluminate mineral phase (CA and CA2), greatly reduces the phosphate dosage and the preparation cost of phosphate aluminate cement, and has excellent coagulation, thickening and mechanical properties.

[0019] Fourthly, the phosphate aluminate cement proposed by the present invention has adjustable setting time, strong early strength and late strength, and excellent CO2 erosion resistance, providing a new type of cementitious material for carbon sequestration. It also has excellent impermeability, sulfate erosion resistance, high temperature resistance, excellent frost resistance and repairability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0021] Figure 1 The XRD diagram of the minerals of the modified aluminate cement clinker of Examples 1 to 4. DETAILED DESCRIPTION

[0022] The present invention can be better understood with reference to the following examples.

[0023] The present invention uses limestone, bauxite and aluminum ash as raw materials, and their chemical compositions are shown in Table 1. Table 1 Chemical composition of raw materials (%)

[0024] The clinker proportions in Examples 1-4 are shown in Table 2.

[0025] Table 2 Phosphate aluminate cement clinker ratio (%) Example 1

[0026] Use a planetary mill to grind each raw material to a fineness of 74μm square hole sieve with a sieve residue of <5%. Weigh the weight percentages as follows: 38% limestone, 15% bauxite, and 47% bauxite. Mix the weighed raw materials for 12 hours to prepare raw material powder; add 5% by weight of tap water or anhydrous ethanol to the raw material powder, mix well, press into 60mm×60mm×5mm square raw material cakes with a press, and dry in a 100℃ blower dryer for 8 hours. After drying, heat the raw material cake to 900℃ at a heating rate of 10℃ / min and keep it warm for 30 minutes, then heat it to 1300℃ and keep it warm for 60 minutes. Then quickly take it out and air-cool it to room temperature to obtain modified aluminate cement clinker. The product XRD pattern is as shown below Figure 1 The quantitative results of clinker minerals are shown in Table 3. The modified aluminate cement is compounded with phosphate and admixtures, and the mixture is placed in a ball mill and mixed for 30 minutes to make it uniformly mixed, thereby obtaining modified aluminate cement-based calcium phosphate aluminate cement. Example 2

[0027] Use a planetary mill to grind each raw material to a fineness of 74μm square hole sieve with a sieve residue of <5%. Weigh the weight percentages as follows: 35% limestone, 15% bauxite, and 50% bauxite. Mix the weighed raw materials for 12 hours to prepare raw material powder; add 5% by weight of tap water or anhydrous ethanol to the raw material powder, mix well, press it into 60mm×60mm×5mm square raw cakes with a press, and dry it in a 100℃ blower dryer for 8 hours. After drying, heat the raw cake to 900℃ at a heating rate of 10℃ / min and keep it warm for 30 minutes, then heat it to 1300℃ and keep it warm for 60 minutes. Then quickly take it out and air-cool it to room temperature to obtain modified aluminate cement clinker. The product XRD pattern is shown as follows Figure 1 The quantitative results of clinker minerals are shown in Table 3. The modified aluminate cement is compounded with phosphate and admixtures, and the mixture is placed in a ball mill and mixed for 30 minutes to make it uniformly mixed, thereby obtaining modified aluminate cement-based calcium phosphate aluminate cement. Example 3

[0028] Use a planetary mill to grind each raw material to a fineness of 74μm square hole sieve with a sieve residue of <5%. Weigh the weight percentages as follows: 34% limestone, 15% bauxite, and 51% bauxite. Mix the weighed raw materials for 12 hours to prepare raw material powder; add 5% by weight of tap water or anhydrous ethanol to the raw material powder, mix well, press it into 60mm×60mm×5mm square raw cakes with a press, and dry it in a 100℃ blower dryer for 8 hours. After drying, heat the raw cake to 900℃ at a heating rate of 10℃ / min and keep it warm for 30 minutes, then heat it to 1300℃ and keep it warm for 60 minutes. Then quickly take it out and air-cool it to room temperature to obtain modified aluminate cement clinker. The product XRD pattern is shown as follows Figure 1 The quantitative results of clinker minerals are shown in Table 3. The modified aluminate cement is compounded with phosphate and admixtures, and the mixture is placed in a ball mill and mixed for 30 minutes to make it uniformly mixed, thereby obtaining modified aluminate cement-based calcium phosphate aluminate cement. Example 4

[0029] Use a planetary mill to grind each raw material to a fineness of 74μm square hole sieve with a sieve residue of <5%. Weigh the weight percentages as follows: 33% limestone, 15% bauxite, and 52% bauxite. Mix the weighed raw materials for 12 hours to prepare raw material powder; add 5% by weight of tap water or anhydrous ethanol to the raw material powder, mix well, press into 60mm×60mm×5mm square raw cakes with a press, and dry in a 100℃ blower dryer for 8 hours. After drying, heat the raw cake to 900℃ at a heating rate of 10℃ / min and keep it warm for 30 minutes, then heat it to 1300℃ and keep it warm for 60 minutes. Then quickly take it out and air-cool it to room temperature to obtain modified aluminate cement clinker. The product XRD pattern is shown as follows Figure 1 The quantitative results of clinker minerals are shown in Table 3. The modified aluminate cement is compounded with phosphate and admixtures, and the mixture is placed in a ball mill and mixed for 30 minutes to make it uniformly mixed, thereby obtaining modified aluminate cement-based calcium phosphate aluminate cement.

[0030] The cement of each of the above embodiments was made into a slurry sample to test the setting time. The preparation steps are as follows: Pour the slurry into a truncated cone mold, cover it with a glass plate, put it into a constant temperature water bath at 25°C and 80°C, and record the time (T0). Use a Vicat instrument to test the setting time of cement slurry. First, place the needle on the surface of the cement slurry. When the needle is inserted 2-3mm from the bottom of the cement slurry, record the time T1 (measured once every 10 minutes); measure once every 5 minutes after initial setting. When the needle can only be inserted into the surface of the cement stone by about 0.5~1 mm, record the time T2. The initial setting time is T1-T0, and the final setting time is T2-T0. The test results are shown in Table 4.

[0031] The cement of each of the above embodiments was made into a slurry sample and tested for 1 day, 3 days and 28 days of strength. The preparation steps are as follows: Pour the prepared cement slurry into a cylindrical mold (φ2.54 cm×2.54 cm), and curing in a constant temperature water bath at 25℃ and 80℃ until demolding 2 hours after final setting. Continue to cure at 25℃ and 80℃ until the specified age and then take it out. After each sample at 80℃ is taken out, it must be immediately placed in water at 27℃±3℃ to cool for 45 minutes, and then the strength of the cement stone is tested using a cement strength tester. Three samples were tested for each group of samples, and the average value was taken. The test results are shown in Table 5.

[0032] The cement of the above embodiments was made into a slurry, poured into a φ2.54 cm×2.54 cm mold, cured in a constant temperature water bath at 25°C and 80°C until final setting, and then demolded 2 h later. The cement stone was dyed with a phenolphthalein solution, placed in a CO2 corrosion test device, and water was added until the mold was completely submerged. The device was sealed, and CO2 was introduced at a pressure of 5 MPa. Then, it was placed at 25°C and 80°C for curing for 1 d, 3 d, and 28 d. The radius of the color change range on the surface of the cement stone was measured using a vernier caliper. The test results of the carbonization depth of the samples are shown in Table 6.

[0033] Table 3 Clinker mineral composition (%)

[0034] Table 4 Setting time of phosphate-aluminate cement slurry (min)

[0035] Table 5 Compressive strength of aluminophosphate cement paste

[0036] Table 6 Carbonation depth of phosphate aluminate cement stone (mm)

[0037] It can be seen from Table 4 and Table 5 that the carbon-sequestered aluminate cement-based phosphate aluminate cement fired by the present invention has a relatively high strength, and the CA / CA2 ratio of the clinker is within the range of 0.5 to 1.5. As the CA / CA2 ratio gradually increases, the setting time of the cement slurry gradually increases. The CA / CA2 ratio in the cement clinker of Example 1 is 3.90, the setting time of the cement slurry is relatively short, and the strength in the later stage also declines. It can be seen from Table 6 that the carbon-sequestered aluminate cement-based phosphate aluminate cement fired by the present invention has a relatively low carbonization depth. As the CA / CA2 ratio in the clinker gradually increases, the carbonization depth gradually increases, but the degree of corrosion is still relatively low. The phosphate aluminate cement fired by the present invention has good CO2 corrosion resistance.

[0038] The phosphate aluminate cement proposed by the present invention has adjustable setting time, strong early strength and late strength, and excellent CO2 erosion resistance, providing a new type of cementitious material for carbon sequestration. It also has excellent impermeability, sulfate erosion resistance, high temperature resistance, excellent frost resistance and repair performance.

[0039] The present invention provides a modified aluminate cement, carbon sequestration phosphate aluminate cement and a preparation method thereof. There are many methods and approaches to realize the technical solution. The above-mentioned specific implementation of the present invention does not constitute a limitation on the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be realized by existing technologies.

Claims

1. A modified aluminate cement, characterized in that: The mineral phase composition is calculated by mass percentage, including CA: 20%~55%, CA2: 10%~50%, C2AS: 25%~35%, C 12 A7: 0.1%~0.2%.

2. The method for preparing the modified aluminate cement according to claim 1, characterized in that: The steps include: (1) crushing, drying, grinding and fully mixing the calcium raw material and the aluminum raw material to obtain raw material; (2) The uniformly mixed raw material is heated to 800-950°C and kept at this temperature for 20-40 minutes, then heated to 1300-1600°C and calcined for 30-100 minutes. After calcination, it is quickly cooled to obtain cement clinker blocks; (3) Grind the obtained cement clinker blocks and mix them thoroughly to obtain the cement clinker.

3. The method for preparing the aluminate cement according to claim 2, characterized in that: In step (1), the calcium raw material is at least one of limestone, quicklime or slaked lime; the aluminum raw material is at least one of bauxite, aluminum ash and aluminum-containing waste slag.

4. The method for preparing the aluminate cement according to claim 2, characterized in that: In step (1), the calcium raw material contains 40% to 55% by mass of CaO; the aluminum raw material contains 50% to 70% by mass of Al2O3; and the raw material is prepared according to a mass composition of 30% to 40% CaO and 50% to 65% Al2O3.

5. The method for preparing the aluminate cement according to claim 2, characterized in that: In step (2), the temperature is first increased to 800-950°C at a heating rate of 5-15°C / min, and kept at that temperature for 30 minutes, and then increased to 1300-1600°C at a heating rate of 5-15°C / min, and kept at that temperature for 30-100 minutes.

6. The method for preparing the aluminate cement according to claim 2, characterized in that: In step (2), after calcination, the mixture is rapidly cooled to room temperature by air cooling, water cooling or liquid nitrogen cooling.

7. A carbon sequestered aluminophosphate cement, characterized in that: The modified aluminate cement according to claim 1 is mixed with phosphate and admixture; wherein the mass percentage of phosphate is 5% to 15%, the mass percentage of admixture is 5% to 20%, and the rest is modified aluminate cement.

8. The carbon sequestered aluminophosphate cement according to claim 7, characterized in that: The phosphate is at least one of trisodium phosphate, sodium dihydrogen phosphate, sodium polyphosphate, tripolyphosphoric acid, sodium metaphosphate and sodium hexametaphosphate.

9. The carbon sequestered aluminophosphate cement according to claim 7, characterized in that: The admixture is at least one of fly ash, slag and silicon powder.

10. The method for preparing carbon-sequestered aluminophosphate cement according to claim 7, characterized in that: The steps include: (1) Grinding the modified aluminate cement and passing it through a 74µm sieve; (2) The modified aluminate cement sieved in step (1) is compounded with phosphate and admixtures, and the mixture is placed in a ball mill and mixed evenly to obtain a cement slurry.